Maternal PTSD and Children's Adjustment: Parenting Stress and Emotional Availability as Proposed Mediators. Issue 6 (3rd August 2016) - Samuelson, Kristin W.; Wilson, Christina K.; Padrón, Elena; Lee, Suellen; Gavron, Lauren
Abstract : Objectives: Maternal posttraumatic stress disorder (PTSD) is a risk factor for negative child adjustment, but it is unclear whether this association is direct (e.g., a mother's PTSD symptoms are observed, learned, and internalized by children which results in behavioral and emotional problems) or indirect, through parent–child relationship difficulties or parenting stress. We hypothesized that parenting stress and maternal emotional availability would exhibit indirect effects on relationships between maternal PTSD and children's functioning. Method: Participants were 52 trauma‐exposed mothers and their children (aged 7–12 years). Mothers completed measures of PTSD and parenting stress and reported on their children's functioning. Emotional availability was assessed through observer‐rated mother–child interactions. Results: Emotional availability was not related to PTSD or child outcomes. Parenting stress had a substantial indirect effect on the relationships between maternal PTSD and child emotion regulation, internalizing, and externalizing behaviors. Conclusions: Results highlight the need to target parenting stress in interventions with trauma‐exposed families.